The Theoretical course of the Good Faith Principle of Jurisprudence and its Reception in Civil Law Brazilian - Pinheiro, Rosalice Fidalgo (2016)
The scope of this article is to demonstrate how the good-faith principle moved away from the formalism into which is was embedded under the aegis of legal positivism of the 19th century, to become the object of jurisprudential creation without, however, totally departing from a certain positivistic rationality.  Restricted to the parameters of forma- lism, it has shown to be too imprecise to be included in a syllogistic way of thinking, which demanded juridical methodology efforts in face of the legislative technique of ge- neral clauses, standards and juridical principles in order to delimit its area of application.  Here is what German courts in the post-war second period achieved; the concretization of the general clause of good-faith into typical legal concepts, the exercise of which re- mains inadmissible: exceptio doli generalis, venire contra facum proprium, Verwirkung, tu quoque, non allegeability of formal nullity, and the unbalanced exercise of rights.  We have limited the topic of this article to the function of good-faith control in the exercise of individual prerogatives in the area of economics, and found that the concept is included in other legal systems that lacked it.  Having chosen to investigate the concept of good- faith in Brazilian jurisprudence, we have submitted the results to critical examination, revealing the specificity of the European juridical tradition in our own Law.  Lastly, we question the limits of a “prêt-a-porter” good-faith to maintain juridical positivism.